Peripheral artery disease, antithrombotic treatment and outcomes in European and Asian patients with atrial fibrillation: analysis from two prospective observational registries - Mei, Davide Antonio; Romiti, Giulio Francesco; Bucci, Tommaso; Corica, Bernadette; Imberti, Jacopo Francesco; Bonini, Niccolò; Vitolo, Marco; Shantsila, Alena; Tse, Hung-Fat; Chao, Tze-Fan; Boriani, Giuseppe; Proietti, Marco; et al. (BMC medicine, 2024)
Background In patients with atrial fibrillation (AF), the impact of peripheral artery disease (PAD) on oral anticoagulant (OAC) therapy use and the risk of outcomes remains unclear. Objective To analyse the epidemiology of PAD in a large cohort of European and Asian AF patients, and the impact on treatment patterns and risks of adverse outcomes. Methods We analysed AF patients from two large prospective observational registries. OAC prescription and risk of outcomes were analysed according to the presence of PAD, using adjusted Logistic and Cox regression analyses. The primary outcome was the composite of all-cause death and major adverse cardiovascular events (MACE). Interaction analyses were also performed. Results Fifteen-thousand-four-hundred-ninety-seven patients with AF (mean age 68.9, SD 11.6 years; 38.6% female, 30% from Asia) were included in the analysis. PAD was found in 941 patients (6.1%), with a higher prevalence among European individuals compared to Asian (8.1% vs 1.2%, p < 0.001). On logistic regression analysis, European patients had sixfold higher odds of presenting with PAD compared with Asians (OR 6.23, 95% CI 4.75–8.35). After adjustments, PAD was associated with lower use of OAC (OR: 0.59, 95% CI: 0.50–0.69). On Cox regression analysis, PAD was associated with a higher risk of the primary composite outcome (HR 1.28, 95% CI: 1.08–1.52) and all-cause death (HR 1.40, 95% CI: 1.16–1.69). A significant interaction was observed between PAD and age, with higher effects of PAD found in younger patients (< 65 years) for the risk of the primary outcome ( p int = 0.014). Conclusions In patients with AF, PAD is associated with lower use of OAC and a higher risk of adverse outcomes, with a greater risk seen in younger patients.